2020
DOI: 10.1136/bmjopen-2020-038370
|View full text |Cite
|
Sign up to set email alerts
|

Impact of frailty on 30-day and 1-year mortality in hospitalised elderly patients with community-acquired pneumonia: a prospective observational study

Abstract: ObjectivesThis study evaluates the impact of frailty, which is a state of increased vulnerability to stressors, on 30-day and 1-year mortality among elderly patients with community-acquired pneumonia (CAP). The main hypothesis is that frailty is an independent predictor of prognosis in elderly CAP patients.DesignProspective, observational, follow-up cohort study.SettingA 2000-bed tertiary care hospital in Beijing, China.ParticipantsConsecutive CAP patients aged ≥65 years admitted to the geriatric department of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
1
15
0
2
Order By: Relevance
“…The pneumonia cases were likely CAP because HAP and VAP were excluded by asking corresponding questions to the participants (see "Outcome variables" in Methods). Our results also suggest that frailty may be an important indicator in the prevention of pneumonia among community-dwelling older adults, not only be an indicator of the mortality in older adults hospitalized for pneumonia as recently reported 11 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The pneumonia cases were likely CAP because HAP and VAP were excluded by asking corresponding questions to the participants (see "Outcome variables" in Methods). Our results also suggest that frailty may be an important indicator in the prevention of pneumonia among community-dwelling older adults, not only be an indicator of the mortality in older adults hospitalized for pneumonia as recently reported 11 .…”
Section: Discussionsupporting
confidence: 86%
“…Several reports have recently shown that frailty was related to mortality in older adults hospitalized due to respiratory infectious diseases [9][10][11] . However, it is unknown whether frailty is associated with susceptibility to and severity of pneumonia in community-dwelling older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst several scales estimating patients’ dependence and functionality [ 24 , 25 , 26 ], we used the FIM, which in a recent study among critically ill elderly patients admitted to an intermediate care unit proved a correlation between low ratings on the scale and higher 1-year mortality rates [ 27 ]. Another research showed that frailty, defined as unintentional weight loss, self-reported exhaustion, weakness, slow walking speed, and low physical activity, was strongly associated with the severity of pneumonia and higher 1-year mortality in older patients, suggesting that frailty should be detected early to improve their management [ 28 ]. In our findings, lower FIM ratings were individually associated with a poorer long-term prognosis but failed in finding significant 1-year mortality correlations in multivariate models.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst several scales estimating patients' dependence and functionality [23][24][25] , we decided to use the FIM, which in a recent study among critically ill elderly patients admitted to an intermediate care unit proved a correlation between low ratings on the scale and higher 1-year mortality rates 26 . Another research showed that frailty, de ned as unintentional weight loss, self-reported exhaustion, weakness slow walking speed, and low physical activity, was strongly associated with the severity of pneumonia and a higher 1-year mortality in older patients, suggesting that frailty should be detected early to improve their management 27 . In our ndings, lower FIM ratings were individually associated with a poorer longterm prognosis but failed in nding signi cant 1-year mortality correlations in multivariate models.…”
Section: Discussionmentioning
confidence: 99%